2018
DOI: 10.1016/j.tranpol.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Technical and operational obstacles to the adoption of electric vans in France and the UK: An operator perspective

Abstract: Since the mid-1990s European urban freight transport has undergone several major changes with direct impact on vehicle use patterns. These include (i) freight vehicle downsizing and (ii) the dieselisation of van fleets (formally referred to as light commercial vehicles or LCVs) More recently, a new possible trend has started to emerge, mainly related to alternative fuelled LCVs for reducing air pollution emissions in urban areas. Electric LCVs up to 3.5 tons are considered a suitable option for last mile opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 13 publications
1
57
0
3
Order By: Relevance
“…For many years, great emphasis has been put on biocomponents and liquid biofuels used in vehicles equipped with internal combustion engines [75,76]. However, an established limit for conventional biofuels and problems encountered in effective production of advanced biofuels, have led to an increased focus on electric propulsion vehicles [77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, great emphasis has been put on biocomponents and liquid biofuels used in vehicles equipped with internal combustion engines [75,76]. However, an established limit for conventional biofuels and problems encountered in effective production of advanced biofuels, have led to an increased focus on electric propulsion vehicles [77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic policies of individual member states promoting renewable energy in the transport sector focus mainly on road transport and the use of biofuels and electric mobility [76]. In Poland, the production of biofuels for many years has been based on raw materials of agricultural origin, such as rapeseed oil and corn [77][78][79]. The trend consisting of basing the market of biofuels on raw food materials has been observed also in the European Union, the USA and Brazil [82][83][84][85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the scenario described above, it is apparent that public outlets and commercial stations will be probably the most critical application in terms of the expected impact on power grids, due to the large number of heterogeneous users (and thus the high stochasticity of power demand profiles) and to the high level of power supply. Several studies recently addressed this concern, by concurring that the large and uncontrolled penetration of EVs would cause relevant issues to the management and operation of distribution networks [4,8,11,12,15]. The main expected adverse impacts include: voltage instability, increase of peak demand, power quality issues (e.g., harmonics and voltage variations), increase of power losses, and degradation of grid equipment (e.g., increase of thermal aging effects in transformers, due to overloading) [8].…”
Section: Saementioning
confidence: 99%
“…Recent studies demonstrated that conventional ICEs are responsible for the emission of the 73% of total urban air pollutants, and also revealed that the growth in chronic health problems in urban areas can be directly related to transportation systems [3]. As a consequence, several restrictions on ICE vehicles have been proposed in European cities, such as the progressive diesel ban in Paris (entered into force since 2015), and the Ultra-Low Emission Zone (ULEZ) that will come into force in London starting from April 2019 [4].Electric Vehicles (EVs), in particular Battery EVs (BEVs), are generally considered the best candidates for the replacement of conventional ICE vehicles, thanks to their independence from the primary energy source, and to the total absence of direct GHG and pollutant emissions. Recent studies demonstrated that BEVs are the less carbon-intensive option if compared to other solutions, such as Plug-in Hybrid EVs (PHEVs) and Hybrid EVs (HEVs) [5], and that the large penetration of EVs could help to significantly reduce indirect GHG emissions and air pollution in urban areas [6,7].Whilst high investment costs and low energy density of batteries are still considered as a relevant limitation to the large penetration of EVs in urban landscapes [8], continuous technology improvements and mass production prospects are leading to rapid cost declines and increases in energy density [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation